Contribution of Social Media Platforms in Tourism Promotion - Omar Salem Seed Gebreel; Ayman Shuayb (LAFADZ JAYA Publisher, 2022)
This study sought to identify the role of social media platforms in tourism marketing and promotion. It was also to evaluate the extent to which social media platforms used to the purpose of tourism promotion in Libya, evaluate they're contributing to promoting tourism sites in Libya, and to evaluate their extent to which they succeeded in promoting tourism sites in Libya. The convenience sampling method was used in this study where the data was obtained from 120 respondents by using a questionnaire. The study concludes that social media platforms play a very sensitive and important role in the effectiveness of tourism marketing and promotion among all users of these media. Additionally, social media platforms have the ability to provide users with accurate and confident information about their destinations which helped them to make accurate decisions about their destinations and tourism sites that they thinking to travel to or visit. Moreover, the users of these platforms mentioned that since these platforms were available to the end-users it was characterized with their ease of use and provide the users of the ability to share and post their experiences and perspectives regarding the sites they visited. This will facilitate the opportunity for tourism destinations to share, marketing, and promoting their contents with their customers effectively and efficiently.